Understanding mechanism of enhanced specific heat of single molten salt-based nanofluids: Comparison with acid-modified salt - Jeong, Seonjin; Jo, Byeongnam (Journal of Molecular Liquids, 2021)
This study aimed to identify the mechanisms for enhancing the specific heat of KNO3-SiO2 nanofluids in both solid and liquid phases. The specific heat of the nanofluids was examined by a different scanning calorimetry, by varying the concentration of the nanoparticle (0.1–10 wt%). The specific heat increased with the nanoparticle concentration but decreased beyond the optimal concentration (1 wt%). The specific heat of the nanofluids was enhanced by up to 24.1% and 28.1% in the solid and liquid phases, respectively. In order to account for the reasons for the enhanced specific heat of the molten salt nanofluids, acid-modified salts in which the aqueous hydrogen peroxide (H2O2) solution was added to KNO3 were prepared, and their specific heat was examined by varying the amount of H2O2. The acid-modified salts showed an enhanced specific heat of 21.1% and 29.5% in the solid and liquid phases, respectively, and similar concentration-dependent specific heat as the nanofluids. Fourier transform infrared spectroscopy and energy-dispersive X-ray spectroscopy as well as scanning electron microscopy were used to corroborate the nanoparticle dispersion into the salt. X-ray diffraction analysis was conducted to compare the crystallite sizes of the nanofluids and acid-modified salts to that of pure KNO3. The reduced crystallite size (increased interfacial area between crystallites) accounts for the enhanced specific heat in the solid phase. Based on the zeta potential measurements, the Stern layer and Debye length, which consist of the electric double layer (EDL), were estimated to be 0.45 and 0.97 nm, respectively, for the KNO3-SiO2 nanofluid. Similar features on the Stern layer and Debye length were obtained for the acid-modified salts. The formation of the EDL adjacent to the nanoparticles accounts for the enhanced specific heat of the nanofluids in the liquid phase.
Keywords: Double layers; H$-2$/O$-2$; Liquid Phase; Liquid phasis; Molten salt; Nanofluids; SiO$-2$; Solid phasis; Solid-phase; Stern layer; Crystallite size; Electric double layer; Molten salt; Nanofluid; Specific heat